Design optimization of gold-coated fiber tips with embedded plasmonic slot nano-resonators. (30th March 2017) - Petropoulou, Afroditi; Zervas, Michalis N; Riziotis, Christos
Abstract: Nanostructures of dimensions around the operating wavelength of light can support optical resonances enhancing the incident light by orders of magnitude and concentrating it in the nanoscale. Their integration to optical fiber tips with thin metallic claddings, forming plasmonic slot nanoresonators (PSNRs), provides ease of light coupling from the fiber's core modes to the slot and a robust platform which can find many applications in nano-optics and sensing. Guiding and modal properties of metal-coated optical fiber tips with embedded PSNRs are investigated through finite element method (FEM) simulations towards the identification of their optimization parameters. It was found that the placement of a PSNR at the cut-off radius of a metal-coated fiber tip, where the group velocity tends to zero, leads to considerable intensity enhancement of the field confined beyond the diffraction limit. Maximum intensity enhancement of optimally placed PSNRs at different radii shows a linear dependence between excitation wavelength and radius, making it feasible to engineer the proper radius for a specific wavelength for maximum enhancement.